Nutritive Value, in vitro Fermentation Characteristics and Nutrient Digestibility of Agro-industrial Byproducts-based Complete Feed Block Enriched with Mixed Microbes - Santoso, B.; Widayati, T.W.; Hariadi, B.Tj. (Pakistan Journal of Nutrition, 2017)
Objective: This study was carried out to evaluate the nutritive value, in vitro fermentation characteristics and nutrient digestibility of agro-industrial byproducts-based complete feed block enriched with mixed microbes. Methodology: The complete feed blocks were mainly composed of agricultural and food industry byproducts such as rice straw, palm oil frond, tofu waste, cassava waste, sago starch and molasses. Four treatments were A, complete feed block without microbe; B, complete feed block containing Lactobacillus plantarum, Saccharomyces cerevisiae and Pseudomonas aeruginosa ; C, complete feed block containing L. plantarum, S. cerevisiae and Acinetobacter baumannii ; D, complete feed block containing L. plantarum, S. cerevisiae, P. aeruginosa and A. baumannii. Lactic acid bacteria, yeast and cellulolytic bacteria were added to the feed block at 107-109 CFU g–1. All complete feed blocks were formulated to be isonitrogenous. About 500 g of mixed ingredients were transferred into a hydraulic press to makes block of size 15×10×8 cm. Results: The feed blocks contained 2.4×106 CFU g–1 L. plantarum, 6.5×104 CFU g–1, 2.7×106 CFU g–1 S. cerevisiae, 2.7×106 CFU g–1 P. aeruginosa and 1.4×105 CFU g–1 A. baumannii. Crude protein content was similar (11.6%) for 4 feed blocks. Addition of cellulolytic bacteria in feed block reduced (p